Origem, amplificação e difusão da preferência manual e sua relação com assimetrias intermanuais de desempenho - Souza, Rosana Machado de (2014)
The effect of using the non-preferred hand on manual preference and motor performance was assessed in two experiments. Experiment 1 investigated the short-term effect of lateralized experience on manual preference and motor performance in infants reaching. Four- and seven-month-olds were induced to use the non-preferred hand through reaching for toys contralaterally to the preferred hand. Reassessment of manual preference in reaching at the central position revealed that infants used the nonpreferred hand more frequently. That behavior was similar between both age groups. Kinematic analysis of reaching did not indicate variations coherent with shift of manual preference. Experiment 2 tested the effect of practice with the non-preferred hand on manual preference and intermanual asymmetries of performance, comparing children and adults. Different tasks requiring reaching and manipulation were practiced. Manual preference was assessed through reaching toward cards at different positions on the right and left of the participant, and inserting the card into a slot. Results showed that use of the nonpreferred hand increased after practice in both age groups. There was no effect of practice on intermanual asymmetries of performance. Results indicate that manual preference is flexible and modulated by immediate lateralized experiences.